Portugal : Third Review Under the Extended Arrangement and Request for Waiver of Applicability of End-March Performance Criteria: Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report, 2012)
This paper presents Portugal's third review under the extended arrangement and request for waiver of applicability of end-March performance criteria. The government has initiated labor market reforms, privatizations, telecom sector liberalization, and improved competition framework. Competitiveness indicators are showing some signs of improvement with wages declining in some sectors and a sizable improvement in the current account deficit in 2011. Although the banking system continues to be heavily reliant on euro system funding, the required adjustment in banks' balance sheets has started.